Malnutrition in remission of childhood cancers as assessed by bioelectric impedance analysis - M. V. Konovalova; A. V. Anisimova; A. Yu. Vashura; E. Z. Godina; D. V. Nikolaev; S. G. Rudnev; O. A. Starunova; I. A. Khomyakova; G. Ya. Tseytlin (Онкогематология, 2014)
The results of our cross-sectional bioimpedance study of children aged 7–17 years cured of cancer during follow-up (patients’ group, n = 552, remission time range 0–15 years) and of age-matched healthy controls (n = 1,500) show significant intergroup differences in body height and body composition parameters. The most pronounced alterations in the patients’ group were observed in standardized values of phase angle reflecting a sharp decrease in the percentage of metabolically active body cell mass in fat-free mass. Malnutrition, judged from the prevalence of obesity and low phase angle, was observed in 52.7 % of our patients reaching a maximum of 76.8 % in a subgroup of children with CNS tumors. In view of known association that exists between malnutrition and reduced tolerance to chemotherapy, increased susceptibility to infections and adverse outcomes rate, we recommend using bioimpedance analysis in remission of childhood cancers in order to monitoring and timely correction of nutritional state as well as for prevention of delayed cardiovascular risks.